Essentials of business communication skills - Ghanekar,Anjali (Everest Publishing Housing, 2010)
Essentials of business communication skills / Ghanekar,Anjali. -- Kolkata: Everest Publishing Housing, 2010 428 G411e4 No. of Copies : 1